2020
DOI: 10.21203/rs.3.rs-41533/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased Expression of UBE2T Predicting Poor Survival of Ovarian Cancer: Based on Comprehensive Analysis of UBE2s, Clinical Samples And the GEO Database

Abstract: Background:Ubiquitin-conjugating enzymes E2 (UBE2) have been reported in the microenvironment of various malignant tumors, but their correlation with ovarian cancer remains elusive. Methods: The Oncomine, GEPIA, Kaplan-Meier Plotter, cBioPortal, and STRING databases were used to systematically analyze the expression pattern, prognostic value, genetic variation, and biological function of 12 members of the UBE2 gene family in ovarian cancer. UBE2T exhibited the greatest correlation with ovarian cancer and was t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, the role of UBE2T in ovarian cancer has not been specifically reported. Based on bioinformatic analysis, Zou et al reported that UBE2T might play a role in the occurrence and development of ovarian cancer [33]; however, the specific mechanism involved in this process has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of UBE2T in ovarian cancer has not been specifically reported. Based on bioinformatic analysis, Zou et al reported that UBE2T might play a role in the occurrence and development of ovarian cancer [33]; however, the specific mechanism involved in this process has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, UBE2T was closely associated to specific immune cells, which were mainly involved in cell cycle-related events, and in Titin and p53 mutations. UBE2T copy number amplification and hypomethylation may be responsible for its upregulation in OV (57). UBE2T overexpression of contributed to the proliferation and metastasis of cervical cancer cells, and UBE2T-overexpressing cervical cancer cells exhibited enhanced self-renewal ability.…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 98%
“…UBE2T overexpression promoted cell proliferation, which was inhibited by UBE2T knockdown. Recently, research has focused on the function of UBE2T in tumorigenesis and tumor progression (57). Previous studies on UBE2T included BrC, bladder cancer (BC), cervical cancer, cholangiocarcinoma, colorectal cancer (CRC), esophageal cancer, lung cancer, hepatocellular carcinoma (HCC/liver HCC), melanoma, nasopharyngeal carcinoma, osteosarcoma, ovarian cancer and pancreatic cancer (PCA).…”
Section: Expression Of Ube2t In Cancermentioning
confidence: 99%